Pengaruh Kompetensi,Motivasi dan Kinerja Pegawai Terhadap Kepuasan Pelanggan PT PLN (Persero) UP3 Palembang - Mulyadi Sinaga; Juhaini Alie (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of employee competence, work motivation, and employee performance on customer satisfaction at PT PLN (Persero) UP3 Palembang. A descriptive quantitative method was used, with data collected through questionnaires distributed to 120 customers. Multiple linear regression analysis was conducted using SPSS version 22. The results indicate that competence, work motivation, and employee performance have a positive and significant effect on customer satisfaction, both partially and simultaneously. The coefficient of determination of 39.7% shows that customer satisfaction is influenced by these three variables. The findings emphasize the importance of human resource management in improving the quality of public services.